Fournier (BRQ) Versus Rusbult (IM): Is Love Really Important in Consumer-Brand Relationship? - Cayolla, Ricardo (2020)
Assuming the meaning and value that brands have for consumers, this paper developed a structured viewpoint in the consumer-brand relationship. This paper explores the fact that there are deep investments by consumers in their relationships with brands. The objectives of the article are, first, to present the two main consumer-brand relationship models (Brand Relationship Quality—BRQ, Investment Model—IM) and, second, to challenge the importance of Love in the relationships established between consumers and brands.